2017
DOI: 10.1095/biolreprod.116.142786
|View full text |Cite
|
Sign up to set email alerts
|

High-fat high-sugar diet induces polycystic ovary syndrome in a rodent model†

Abstract: Obesity has been linked with a host of metabolic and reproductive disorders including polycystic ovary syndrome (PCOS). While a clear association exists between obesity and PCOS, the exact nature of this relationship remains unexplained. The primary symptoms of PCOS include hyperandrogenism, anovulation, and polycystic ovaries. Most animal models utilize androgen treatments to induce PCOS. However, these models often fail to address the underlying causes of the disease and do not effectively reproduce key meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 51 publications
1
27
2
1
Order By: Relevance
“…In our previous study, we found an increase in follicular cysts and decrease in CL as a result of a HFHS diet [ 21 ]. However, in the present study, the rats were maintained on the diet for a longer period (4 additional weeks).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we found an increase in follicular cysts and decrease in CL as a result of a HFHS diet [ 21 ]. However, in the present study, the rats were maintained on the diet for a longer period (4 additional weeks).…”
Section: Resultsmentioning
confidence: 99%
“…However, although a clear connection exists between obesity and reproductive impairment, the underlying mechanisms are unclear. In our previous study, we used a high-fat, high-sugar (HFHS) diet to induce obesity in rats and demonstrated the appearance of multicystic ovaries and disrupted estrous cyclicity, both indicators of reproductive impairment [ 21 ]. The diet, administered after weaning, provides a method to examine the natural progression of these adverse reproductive impairments as they develop.…”
mentioning
confidence: 99%
“…Likewise, Nino et al (37) found that a high-carbohydrate diet was able to increase the number of atretic follicles in rats. Furthermore, Roberts et al (38) have shown that animals fed a high-fat, high-sugar diet had higher frequency of cystic follicles when compared to control animals. It is yet unclear how the ingestion of HSD or other types of hypercaloric diets lead to ovarian dysfunction, however feasible underlying mechanisms include: hyperinsulinemia culminating in higher production of ovarian androgens in synergy with the luteinizing hormone (10), increased expression of anti-mullerian hormone in granulosa cells (19) and increased production of reactive oxygen species (39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the impaired LH surge may result in the development of cystic ovaries in this model. In a similar study from the same group, rats that received the HDHS diet for 11 weeks manifested hyperinsulinemia but not hyperandrogenemia [74]. In addition, the authors analysed changes in gene expressions caused by the HDHS diet in the ovary; the expressions of ovarian genes related to the primary follicle stage (e.g., epiregulin, Ereg ), estrogen metabolism (e.g., Cbr1 or Ste2 ), and insulin receptors ( Insrr ) were mostly shifted.…”
Section: Methodsmentioning
confidence: 99%